Best Practices in Data Collection and Instrument Development: An Applicative Guide for Quantitative Researchers - Ahmad Abdullah Faqih; Nashrullah Nashrullah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
Quantitative research requires appropriate data collection techniques and quality research instruments to produce valid and reliable findings. The purpose of this study is to describe various data collection techniques in quantitative research along with the systematic process of developing research instruments that meet psychometric standards. This research uses a literature review method by comprehensively analyzing research methodology literature from various credible academic sources, including research methodology textbooks and indexed scientific journal articles. Data analysis was conducted using content analysis methods with a thematic approach to identify main themes related to data collection techniques and the development of quantitative research instruments. The research results show that quantitative data collection techniques include surveys, experiments, structured observations, and the use of secondary data, where the selection of appropriate techniques must be adjusted to population characteristics, types of information needed, and available resources. Quality research instruments must meet validity criteria that ensure the instrument measures the intended construct and reliability that guarantees measurement consistency. The instrument development process involves systematic stages from conceptual and operational definition of variables, clear item writing, content validation by experts, instrument testing, to psychometric analysis using appropriate statistical techniques. Contemporary challenges in quantitative research include adaptation to digital transformation through online surveys, utilization of big data, handling declining response rates, and ethical considerations regarding privacy and informed consent. This research concludes that the integration of methodological rigor, technological innovation, and ethical sensitivity is key to producing quantitative research that is not only technically valid and reliable, but also socially responsible and capable of making meaningful contributions to the development of knowledge and evidence-based decision making.